Assessment of Seasonal Variations of PM10 Concentration in Perak, Malaysia - Musbah, Mohd Fadhil (IRC, 2019)
The aim of this project is to find the relationship between the seasonal variations in Perak with the concentration of PM10 using the data provided by Alam Sekitar Malaysia Berhad (ASMA) covering the year of 2015. The interaction between PM10 particles and climate parameters is complicated and requires thorough investigation to understand the significance of weather parameters to the concentration of PM10 that exists in the atmosphere. PM10 concentration has always been a problem when it comes to maintaining the quality of the atmosphere.